A Mingling of Ghosts: A Response to Daniel Butler's "Racialized Bodies and the Violence of the Setting". Issue 3 (3rd July 2019) - Swartz, Sally
ABSTRACT: In this brief commentary on Butler's description of ruptures and violences of setting, so dense with possibilities for debate and elaboration, four central themes are explored: a rumination on the word "visceral, " suggesting that nonbelonging is never a ghostly experience; "plucking up a protest, " and the paradox of needing for a place of belonging before protest is possible; the bewildering multiplicity of ghosts in protest movements; and how we think of belonging in a clinical setting.